Gender Role in Rural Life: An Audience Reception Analysis on Banyumas Films in Reformation Era - Aidatul Chusna; M. Taufiqurrohman; Lynda Suzanna (Bina Nusantara University, 2017)
This qualitative research was aimed at investigating audience’s responses on gender role in rural life represented in Banyumas films. The data were taken from library research, questionnaire, and group discussion with Banyumas natives. The audience consisted of female and male university students as well as Banyumas film community. Media viewing was conducted before the discussion. The study findings show that the audiences, both males and females, tend to be receptive to the shifting role of wife as the breadwinner of the family since factories in Banyumas give more work opportunities to women than men. In addition, the respondents are appreciative to the role of Banyumas women who are actively involved in the cultural preservation. However, they think that it rarely happens as Banyumas people prefer working in factories to preserve the tradition.